Therapeutic Effects of Forest Bathing on Human Health: A Systematic Review - Adrianna Samoraj; Jakub Zajączkowski; Paulina Krzeszowska; Kacper Stępniak; Karolina Marrodán-Wojtczak; Jan Wilk; Jakub Jarmołowicz; Aleksandra Kujawa; Karolina Krochmal; Radosław Kuźma (Journal of Education, Health and Sport)
Introduction and Purpose: This comprehensive review aims to synthesize and analyze the existing scientific literature concerning the multifaceted impact of forest bathing, also known as shinrin-yoku, on human health and overall well-being. We will delve into the historical origins of shinrin-yoku while also meticulously examining the specific health domains.